If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 15 = 4 + -2x Reorder the terms: 15 + 9x = 4 + -2x Solving 15 + 9x = 4 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 15 + 9x + 2x = 4 + -2x + 2x Combine like terms: 9x + 2x = 11x 15 + 11x = 4 + -2x + 2x Combine like terms: -2x + 2x = 0 15 + 11x = 4 + 0 15 + 11x = 4 Add '-15' to each side of the equation. 15 + -15 + 11x = 4 + -15 Combine like terms: 15 + -15 = 0 0 + 11x = 4 + -15 11x = 4 + -15 Combine like terms: 4 + -15 = -11 11x = -11 Divide each side by '11'. x = -1 Simplifying x = -1
| 9x-7(x+2)=10 | | 9x-7(y+2)=10 | | 3x-3=4+2x | | y=ax^2+b | | 9x=4-2x | | y+(-39)=-43 | | 18=26x-34 | | 82+(-20)= | | 8x+13y=2700 | | 4x^2+9-45=0 | | ysinx-xy^2=c | | ysenx-xy^2=c | | x^2-8x+16=-27 | | -41+(-25)= | | (x^(3/8))(x^(-7/10)) | | -3(x+2)-42=5-38 | | -41+(-15)= | | 12x+15=9(x+8) | | (3x+1)(x+2)=0 | | cosx=-0.72 | | y+(-22)=-46 | | (-7x+1)(10x+9)= | | (3m+1)(mx+2)=0 | | 15+y=13 | | 191=23x-85 | | -9-6=10x+9-9x | | -9-6=10x+9-9 | | -7(x+2)-13=14+8 | | 12x-51=6 | | 8(y+3)=24 | | 85-23+x=191 | | 5x^2+11y^2+16xy-36=0 |